2021
DOI: 10.3389/fonc.2021.681629
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Effects of Histotripsy for Cancer Therapy

Abstract: Cancer is the second leading cause of death worldwide despite major advancements in diagnosis and therapy over the past century. One of the most debilitating aspects of cancer is the burden brought on by metastatic disease. Therefore, an ideal treatment protocol would address not only debulking larger primary tumors but also circulating tumor cells and distant metastases. To address this need, the use of immune modulating therapies has become a pillar in the oncology armamentarium. A therapeutic option that ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 138 publications
(229 reference statements)
3
31
0
Order By: Relevance
“…These results are in line with previous investigations of histotripsy's immunostimulatory potential [9,12,15,16,[18][19][20][21] and suggest that a single histotripsy ablation can alter the local tumor immune microenvironment. Although there were no statistically significant differences between pre-and posttreatment cytokine concentrations for any of the analytes, it is possible that changes were missed due to the timing of cytokine data analysis in this study, which was conducted at various time points prior to histotripsy treatment and surgical removal.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These results are in line with previous investigations of histotripsy's immunostimulatory potential [9,12,15,16,[18][19][20][21] and suggest that a single histotripsy ablation can alter the local tumor immune microenvironment. Although there were no statistically significant differences between pre-and posttreatment cytokine concentrations for any of the analytes, it is possible that changes were missed due to the timing of cytokine data analysis in this study, which was conducted at various time points prior to histotripsy treatment and surgical removal.…”
Section: Discussionsupporting
confidence: 92%
“…In addition to its ablative potential, histotripsy may also promote immunostimulatory effects related to its ability to induce immunogenic cell death [16]. Studies of HIFU in rodent tumor models have demonstrated that HIFU is immunogenic and that histotripsy may result in more robust immune responses than thermal HIFU [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early preclinical results suggest that histotripsy may elicit an immune response. For example, mouse studies in GBM models treated with focused ultrasound released tumor antigens and recruited and activated immune cells, changing the tumor microenvironment from cold to hot [36]. To date, there are no clinical trials with histotripsy for brain tumors.…”
Section: Histotripsymentioning
confidence: 99%
“…The OS tumor microenvironment (TME), like other cancers, is immunosuppressive, allowing cancer cells to evade the immune response and proliferate and form malignant tumors [45,46]. We hypothesized that histotripsy treatment would modulate the immunosuppressive OS TME and stimulate a proinflammatory anti-tumor immune response, which has previously been reported to be associated with histotripsy treatment [47][48][49][50]. The stimulation of a pro-inflammatory immune response would lead to infiltration of proinflammatory macrophages, characterized by double positive staining of IBA1 and iNOS and potentially an infiltration of lymphocytes.…”
Section: Discussionmentioning
confidence: 99%